Analogous graphite carbon sheets derived from corn stalks as high performance sodium-ion battery anodes. Issue 108 (8th November 2016) - Qin, Decai; Zhang, Fang; Dong, Shengyang; Zhao, Yanzhang; Xu, Guiyin; Zhang, Xiaogang
Abstract : Analogous graphite carbon sheets from corn stalks have been synthesized via a simple high temperature carbonization and expansion process, which showed superior sodium ion storage performance. Abstract : Biomass derived carbon (BMC) materials have attracted much attention due to their high performance and abundant sources. Herein, analogous graphite carbon sheets (AGCS) from corn stalks have been synthesized via a simple high temperature carbonization and expansion process. A morphology study showed that the obtained carbon sheets retained the natural cross-sectional honeycomb-like shape and the longitudinal hollow tubular array structure of the corn stalks, which provided abundant macropores and micropores to facilitate sodium ion transportation and electrolyte diffusion. X-ray diffraction analysis showed that the interlayer spacing of the carbon sheets is larger (0.384 nm) than that of graphite (0.335 nm), which allowed sodium ion to be de/intercalated. When used as an anode for sodium ion batteries, the sample carbonized at 1200 °C (AGCS-1200) showed a better sodium ion storage performance than that carbonized at 900 °C (BMC-900). AGCS-1200 exhibits a stable reversible capacity of 231 mA h g −1 after 200 cycles at 0.25C (1C = 200 mA g −1 ), while the capacity value for BMC-900 was 162 mA h g −1 after 100 cycles. What's more, a better rate capability for AGCS-1200 (232, 136 mA h g −1 ) than that of BMC-900 (125, 68 mA h g −1 ) at rates of 1C and 5C, respectively, is demonstrated. Significantly, the AGCs-1200 anode shows an excellent long-term cycling stability, which delivers a capacity of 42 mA h g −1 after 2000 charge–discharge cycles at a very high rate of 15C.